Avian influenza virus: new features related to its pathogenicity and strategies for fighting against it - Cabezas Fernández del Campo, José Antonio (Real Academia Nacional de Farmacia, 2009)
Since Taubenberger´s team recreated each of the genes of influenza virus that caused the terrible pandemic of 1918-19 using the technique called reverse genetics and checked the infectious capacity of the newborn virus, it seems that its high pathogenicity may be due to disregulation of the innate immune mechanisms normally performed by the cytokines of host cell. Furthermore, the H5N1 subtype of avian influenza, which also causes a similar dysfunction, has higher pathogenicity than that of 1918-19 influenza virus. Assays to prevent the mild, moderate or severe risks of an eventual future pandemic affecting humans caused by the H5N1 subtype are now being carried out by preparing new vaccines and neuraminidase (= sialidase) inhibitors such as oseltamivir and zanamivir, as well as other agents that block the function of several components of the virus. Recently, has been debated whether it would be convenient to use modulators of the immune system, such as statins, against the secondary effects of the viral infection caused by the disregulation mechanisms of cytokines, to reinforce the above therapeutic measures. The low cost of statins offers additional justification for their use. Reconstruido por ingeniería genética el virus que causó la terrible pandemia de gripe de 1918-19 y comprobada su capacidad de infección, se ha deducido que la gran patogenicidad del mismo puede deberse a una desregulación de los mecanismos inmunitarios que ejercen normalmente citocinas de las células hospedadoras. Asimismo, el subtipo H5N1 del virus de la gripe aviar, por una desregulación análoga, posee una patogenicidad que es aún mayor que la del subtipo de virus de la gripe de 1918-19. Intentos para prevenir los riesgos (leves, moderados o muy graves) de la esperada pandemia que produciría en humanos el subtipo H5N1 -u otros subtipos peligrosos que puedan surgir- se están efectuando con la preparación de nuevas vacunas, así como mediante la interrupción del ciclo biológico del virus con inhibidores de la enzima vírica neuraminidasa (= sialidasa), tales como el oseltamivir y el zanamivir, o con diversos agentes que bloquean el funcionamiento de otros componentes de dicho virus. Últimamente, se está analizando si es o no conveniente tratar de reforzar estas medidas con el uso de moduladores de ciertas citocinas, tales como algunas estatinas u otros compuestos de acción e índole varias, cuyo reducido coste -por pertenecer al grupo de los “genéricos”- constituye un aliciente adicional.